Optimalisasi Pembelajaran Tahfidz Al-Qur’an melalui Pemanfaatan Teknologi Digital di Sekolah Umum: Studi Kualitatif di SMP Negeri 20 Makassar - Hardianti H Hardianti H; Imas Masripah (MAN 4 Kota Pekanbaru, 2026)
Tahfidz Al-Qur’an learning in public schools often faces significant challenges due to limited instructional time, resulting in less optimal memorization and repetition (muroja’ah) processes. In response to these constraints, the integration of digital technology offers a potential solution to extend learning beyond classroom boundaries. This study aims to analyze the utilization of digital technology in Tahfidz Al-Qur’an learning at SMP Negeri 20 Makassar and examine its role in addressing time limitations in formal education settings. This research employed a qualitative approach with a descriptive design. Data were collected through observations, in-depth interviews with Tahfidz teachers and students, and documentation analysis. The findings reveal that the use of digital platforms such as WhatsApp, murottal audio-visual media, and digital Qur’an applications significantly supports students in conducting independent memorization and repetition. Furthermore, digital technology enables continuous monitoring of students’ memorization progress outside school hours and enhances their learning motivation. This study concludes that the integration of digital technology contributes to improving the flexibility, continuity, and effectiveness of Tahfidz Al-Qur’an learning in public schools. This approach reflects an adaptive pedagogical response to limited instructional time, while also demonstrating how digital platforms can extend learning beyond classroom settings and support continuous monitoring of students’ memorization processes.